PENGARUH INDEPEDENSI DAN PROFESIONALISME KARYAWAN SERTA PERANAN BADAN PENGAWAS TERHADAP EFEKTIFITAS STRUKTUR PENGENDALIAN INTERN DALAM PEMBERIAN KREDIT DI LEMBAGA PERKREDITAN DESA SEKECAMATAN BANGLI - I Made Mastra (Universitas Pendidikan Nasional, 2017)
LPD is one of the assets and income for culterel village. So that LPD need for the good and realiable management. LPD should have adequate internal and external control to preverent abuses of power various parties that can lead bangkruptcy in.LPD LPDshould observe the provision of credit to minimize the bad debts. The purpose of this research is to determine how much influence, independence professionalism and supervicory board on the effectiveness of the internal control structure in the provision of credit in LPD Bangli. The analysis technique used is validity test, reability test, classic assumption test and multiple linear regression test and also hypothesis test consist og F–test and T- test based on the survey result all of the variables in this research instrument are declared free of the interference classical assumption. The multiple regression analysis (F-test) explain that the influence of the independence professionalism and suvervisory board a significant positive impact on the efectivness of the internal control structure in the provision of credit in LPD Bangli. T-test found the three variables (inthepedence, professionalism, and suvervisory board) are declared partial significant positive effect on the effectiveness of the internal control structure in the provision of credit in LPD Bangli.Keywords: Indepedence professionalism, employess supervisory board and the effectiveness of the internal control structure.